MEIOK21: a new component of meiotic recombination bridges required for spermatogenesis. Issue 12 (28th May 2020) - Shang, Yongliang; Huang, Tao; Liu, Hongbin; Liu, Yanlei; Liang, Heng; Yu, Xiaoxia; Li, Mengjing; Zhai, Binyuan; Yang, Xiao; Wei, Yudong; Wang, Guoqiang; Chen, Zijiang; et al.
Abstract: Repair of DNA double-strand breaks (DSBs) with homologous chromosomes is a hallmark of meiosis that is mediated by recombination 'bridges' between homolog axes. This process requires cooperation of DMC1 and RAD51 to promote homology search and strand exchange. The mechanism(s) regulating DMC1/RAD51-ssDNA nucleoprotein filament and the components of 'bridges' remain to be investigated. Here we show that MEIOK21 is a newly identified component of meiotic recombination bridges and is required for efficient formation of DMC1/RAD51 foci. MEIOK21 dynamically localizes on chromosomes from on-axis foci to 'hanging foci', then to 'bridges', and finally to 'fused foci' between homolog axes. Its chromosome localization depends on DSBs. Knockout of Meiok21 decreases the numbers of HSF2BP and DMC1/RAD51 foci, disrupting DSB repair, synapsis and crossover recombination and finally causing male infertility. Therefore, MEIOK21 is a novel recombination factor and probably mediates DMC1/RAD51 recruitment to ssDNA or their stability on chromosomes through physical interaction with HSF2BP.